2021
DOI: 10.3390/ijerph18168649
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Proposal of Tele-Exercise Based on “Square Stepping Exercise” in Preschoolers: Study Protocol

Abstract: Early childhood education aims to achieve the motor, cognitive, emotional, and social development of preschoolers by providing them with a variety of learning opportunities. The square-stepping exercise (SSE) is a balance and lower limb strength training programme used to prevent falls and stimulate cognitive function in older adults. This project aims to propose an SSE tele-exercise (Tele-SSE) protocol to evaluate its effects on the motor and cognitive development of children aged between 3 and 6 years. A ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It has been reported that SSE stimulates these three core executive functions and improves aspects such as problem-solving ability, inference, and mental flexibility in young adults (Kawabata et al 2021 ). In addition, SSE involves classical patterns of activity, such as walking and jumping, and has shown a positive effect on the motor and cognitive abilities of children (Dominguez-Munoz et al 2021 ). Notably, although there is no direct scientific evidence, studies on the positive effects of exercise on immunity (Walsh and Oliver 2016 ) suggest that regular SSE participation could lead to beneficial changes in immune cell populations and function.…”
Section: Square Stepping Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that SSE stimulates these three core executive functions and improves aspects such as problem-solving ability, inference, and mental flexibility in young adults (Kawabata et al 2021 ). In addition, SSE involves classical patterns of activity, such as walking and jumping, and has shown a positive effect on the motor and cognitive abilities of children (Dominguez-Munoz et al 2021 ). Notably, although there is no direct scientific evidence, studies on the positive effects of exercise on immunity (Walsh and Oliver 2016 ) suggest that regular SSE participation could lead to beneficial changes in immune cell populations and function.…”
Section: Square Stepping Exercisementioning
confidence: 99%
“…The SSE program is an educational psychomotor intervention activity for the development of motor and cognitive abilities from children to the elderly, regardless of age. SSE enhances cognitive control, improving working memory and cognitive flexibility, and also functions required to plan and execute actions to achieve goals, including problem solving (Dominguez-Munoz et al 2021 ; Kawabata et al 2021 ).…”
Section: Square Stepping Exercisementioning
confidence: 99%
“…Therefore, early childhood education aims to achieve the motor, cognitive, emotional, and social development of preschoolers by providing them with various learning opportunities. [13], however, at least the teacher's understanding in providing learning [14]. The importance of experiencing movement skills from an early age for a child who will become an athlete later, and what needs to be understood here is that not only children who become athletes need various kinds of experience and movement skills at an early age so that children have good hard skills [15].…”
Section: Introductionmentioning
confidence: 99%
“…The SSE is an intervention that is rarely used in children [ 55 , 56 ], although it offers numerous advantages, such as being low cost, portable, adaptable, and modifiable, with different levels of difficulty and options to include different kinds of aids. Thus, we aim to analyse the effects of an SSE training program in motor (balance), sensory processing (sensory patterns, systems, and adaptive behaviour) and cognitive (attention and executive function) skills in children and adolescents with ASD.…”
Section: Introductionmentioning
confidence: 99%